2009
DOI: 10.1029/2008jb006092
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on mineralization, fluid‐rock interaction, and mass transfer during faulting at 2–3 km depth from the SAFOD drill hole

Abstract: [1] Mineralogical and geochemical changes in mudrock cuttings from two segments of the San Andreas Fault Observatory at Depth (SAFOD) drill hole (3066-3169 and 3292-3368 m measured depth) are analyzed in this study. Bulk rock samples and hand-picked fault-related grains characterized by polished surfaces and slickensides were investigated by X-ray diffraction, electron microscopy, and geochemical analysis. The elemental changes in fault-related grains along the sampled San Andreas Fault are attributed to disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 54 publications
3
31
1
Order By: Relevance
“…These results support the model of a weak fault in an otherwise strong crust. Various observations have been made on the natural samples with a view to understanding creep mechanisms [ d ' Alessio et al ., ; Gratier et al ., ; Hadizadeh et al ., ; Holdsworth et al ., ; Janssen et al ., , ; Moore and Rymer , ; Schleicher et al ., , ; Solum et al ., ; Zoback et al ., ]. The study by Holdsworth et al .…”
Section: San Andreas Fault and Safod Boreholementioning
confidence: 99%
See 1 more Smart Citation
“…These results support the model of a weak fault in an otherwise strong crust. Various observations have been made on the natural samples with a view to understanding creep mechanisms [ d ' Alessio et al ., ; Gratier et al ., ; Hadizadeh et al ., ; Holdsworth et al ., ; Janssen et al ., , ; Moore and Rymer , ; Schleicher et al ., , ; Solum et al ., ; Zoback et al ., ]. The study by Holdsworth et al .…”
Section: San Andreas Fault and Safod Boreholementioning
confidence: 99%
“…The original contribution of the study is to show the possible change in deformation with time with considerable transformation of the rocks, with regard to both their composition and their structure. This change in composition and structure is studied through the identification of deformation mechanisms, based on new microstructural observations, and on data already published in other papers [ Gratier et al ., ; Hadizadeh et al ., ; Holdsworth et al ., ; Janssen et al ., , ; Mittempergher et al ., ; Schleicher et al ., , ; Solum et al ., ; Zoback et al ., ]. To the author's knowledge, this time‐dependent change has never been discussed in such detail up till now.…”
Section: Introductionmentioning
confidence: 99%
“…Geodetic measurements reveal a permanent displacement rate of about 28 mm/year at its maximum over a narrow zone of less than 20 m (Titus et al, 2006). Bore hole drilling through the SAF allowed to correlate fault rock microstructures with real time geophysical data and therefore provides useful information to identify aseismic mechanisms (Bradbury et al, 2011;Holdsworth et al, 2011;Schleicher et al, 2009;Solum et al, 2006;Zoback et al, 2010).…”
Section: -Steady State Pressure Solution Creep Law: Modelling An Aseimentioning
confidence: 99%
“…In seismogenic faults, brecciation during a seismic event would destroy fault rock cohesive strength [Sibson, 1986b], which is then regenerated during the interseismic period through fault healing processes [Sleep and Blanpied, 1992;Karner et al, 1997;Marone, 1998b;Muhuri et al, 2003;Tenthorey and Cox, 2006;Niemeijer et al, 2008]. A mechanism for weakening at a longer timescale is the authigenic formation of weak, phyllosilicate phases by fluid-rock interactions, facilitated by grain size reduction [Wintsch et al, 1995;Vrolijk and van der Pluijm, 1999;Warr and Cox, 2001;Jefferies et al, 2006] which has been observed in fault systems such as the San Andreas [Evans and Chester, 1995;Schleicher et al, 2009Schleicher et al, , 2010Holdsworth et al, 2011]. The presence and/or development of phyllosilicate minerals can also contribute to weakening by developing a frictionally weak, throughgoing foliation in the rock as demonstrated in the laboratory using rock analog material [Bos et al, 2000;Niemeijer and Spiers, 2005] and natural fault rock [Collettini et al, 2009b].…”
Section: Implications For Slip Behavior In Natural Fault Systemsmentioning
confidence: 99%